Photoconductivity mechanism in structures with Ge-nanoclusters grown on Si(100) surface - Melnichuk, Ye.Ye.; Hyrka, Yu.V.; Kondratenko, S.V.; Kozyrev, Yu.N.; Lysenko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Interband optical transitions in the epitaxial Si/Ge heterostructures with Ge
nanoislands grown on Si(100) surface were investigated using photocurrent
spectroscopy. The mechanism of photoconductivity was discussed. It was shown that
electron transitions from the ground state of the valence band in a quantum dot to the
conduction band of Si surrounding make the main contribution into monopolar
photoconductivity below the fundamental absorption edge of crystalline Si. Photoexcited
holes were found to be localized in Ge nanoislands inducing the lateral conductivity
changes in the near-surface depletion layer of p-Si substrate due to the field-effect.